Sensitivity studies and optimization of arrangements of optically pumped magnetometers in simulated magnetoencephalography. Issue 3 (7th May 2019) - Eichardt, Roland; Strohmeier, Daniel; Hunold, Alexander; Machts, René; Haueisen, Jens; Oelsner, Gregor; Schmidt, Christian B.; Schultze, Volkmar; Stolz, Ronny; Graichen, Uwe
Abstract : Purpose: The purpose of this paper is to present a simulation study using a model of a new optically pumped magnetometer sensor for application in the field of magnetoencephalography. The effects of sensor distance and orientation on the measurement information and the sensitivity to neuronal sources are investigated. Further, this paper uses a combinatorial optimization approach for sensor placement to measure spontaneous activity in the region of the occipital cortex. Design/methodology/approach: This paper studies the effects of sensor distance and orientation on sensitivity to cortical sources and measurement information. A three-compartment model of the head, using the boundary element method, is applied. For sensor setup optimization, a combinatorial optimization scheme is developed. Findings: The sensor distance to sources considerably affects the sensitivity and the retrieved information. A specific arrangement of four sensors for measuring spontaneous activity over the occipital part of the head is optimized by effectively avoiding position conflicts. Research limitations/implications: Individual head models, as well as more detailed noise and signal models, will increase the significance for specific-use cases in future studies. Originality/value: Effects of sensor distance and orientation are specifically evaluated for a new optically pumped magnetometer. A discrete optimization scheme for sensor optimization is introduced. The presented methodology is applicable for other sensor characterization and optimization problems. The findings contribute significantly to the development of new sensors.